2015
DOI: 10.1074/jbc.m115.643015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Cholesteryl Ester Transfer Protein Expression and Reverse Cholesterol Transport by Inhibition of DNA Topoisomerase II

Abstract: Background: CETP expression mediates cholesterol metabolism and the development of atherosclerosis. Results: Inhibition of Topo II activates CETP expression in HepG2 cells and CETP transgenic mouse liver, which was associated with increased reverse cholesterol transport in vivo. Conclusion: Topo II inhibitors induced CETP expression and RCT by activating LXR pathway. Significance: We found an important function of Topo II inhibition in regulating cholesterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Etoposide is a semisynthetic agent that binds to and inhibits topoisomerase II, preventing repair of DNA breaks. To date there are no reports of etoposide‐induced steatosis, although it does impact cholesterol metabolism through its effects on hepatic cholesteryl ester transfer protein . EPOCH‐R also differs from R‐CHOP in the delivery of doxorubicin (infusional versus bolus), which may impact hepatic toxicity, and in a higher prednisone dose, although this is unlikely to result in a delayed effect.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide is a semisynthetic agent that binds to and inhibits topoisomerase II, preventing repair of DNA breaks. To date there are no reports of etoposide‐induced steatosis, although it does impact cholesterol metabolism through its effects on hepatic cholesteryl ester transfer protein . EPOCH‐R also differs from R‐CHOP in the delivery of doxorubicin (infusional versus bolus), which may impact hepatic toxicity, and in a higher prednisone dose, although this is unlikely to result in a delayed effect.…”
Section: Discussionmentioning
confidence: 99%
“…It aids in the transportation of fat phosphate, which is a constituent of HDL particles [237]. Additionally, LXRs regulate the gene expression of cholesteryl ester transfer protein (CETP), which is accountable for the transfer of cholesterol from HDL to other lipid particles [238].…”
Section: Er Stress and Nuclear Receptors In Adipogenesismentioning
confidence: 99%
“…In dyslipidaemic animals, anacetrapib increased RCT, whereas an equipotent dose of dalcetrapib reduced it. Liu et al ( 2015 ) found that inhibition of DNA topoisomerase II (Topo II) by etoposide, tenipooside or Topo II siRNA increased CETP gene expression and CETP secretion in HepG2 cells. When given to CETP transgenic mice, teniposide induced CETP expression in the liver, and increased macrophage-to-feces RCT to a greater degree than in wild-type mice with no CETP.…”
mentioning
confidence: 99%